Celebrity Endorsements in Glo and Pepsi Advertisements on Consumer Buying Patterns in South-South Nigeria - Oghenekevwe, Oghiagbepha; Nkemdilim, Ijeh Patrick; Emmanuel, Emmanuel Biri (Master Program of Sociology, Universitas Malikussaleh,, 2024)
This study investigated celebrity endorsement in Glo and Pepsi advertising and consumer purchasing behaviour in South-South, Nigeria. The study acknowledged contemporary society that is characterized with globalization and competition, because most consumers are exposed to alternative product. These propel business organizations to employ the most effective methods, strategies and programmes in producing and marketing their products and services. However. The study was focused to find out celebrity trustworthiness and consumer purchasing behaviour among Pepsi and Glo customers in South-South, Nigeria and identify celebrity expertise and consumer purchasing behaviour among Pepsi and Glo customers in South-South, Nigeria. The study employed the ex-post facto research design and applied the survey method involving 1200 respondents and adopted comparison of percentages, mean and standard deviation for data analysis. The study theoretical perspective was drawn from perception theory of. Data gathered were analysed using descriptive statistics such as frequency counts and measures of central tendencies while mean and standard deviation was used to answer the research questions. Result from the study showed that there was a significant relationship between celebrity endorsement and consumer purchasing behaviour among Pepsi and Glo customers in South-South, Nigeria. Based on the result, it is recommended that both the Pepsi and Glo companies should ensure proper implementation of policy for celebrity endorsement as this will enhance a better behaviour from their consumers in the South-South geo-political zone.